Fifteen-minute consultation: public health for paediatricians—adolescent public health. Issue 5 (4th July 2016) - Hargreaves, Dougal S; Williams, Bhanu; Straw, Fiona; Gregorowski, Anna; Yassaee, Arrash; Devakumar, Delan
Abstract : Paediatricians have a key role to play in ensuring a holistic, integrated approach is taken to meeting adolescent health needs. There is increasing evidence that failure to do so can lead to poor healthcare experience, avoidable ill health and increased need for healthcare services, both in the short term and in adult life. This article aims to guide paediatricians in answering the questions 'How well are the public health and clinical needs of the adolescent population in my area being met? And how can we improve?'